RESPON PERTUMBUHAN BIBIT KELAPA SAWIT DI MAIN NURSERY AKIBAT KOMBINASI PUPUK KOTORAN AYAM DAN NPK PADA TANAH PMK - Niko Wiranata; Warganda Warganda; Agus Ruliyansyah (Fakultas Pertanian Universitas Tanjungpura, 2022)
Seedlings of oil palm in the main nursery take place from the age of 4 to 12 months of seedlings, in that period the oil palm seedlings already need additional nutrients in the growing media. Utilization of PMK soil as a growing medium is faced with low soil fertility, low levels of organic matter availability, and lack of nutrient content. The limited carrying capacity of PMK soil needs to be overcome by adding organic matter and nutrients to improve soil fertility of PMK as a growing medium for nurseries in the main oil palm nursery. This study aims to determine the effect and dose of the best combination of chicken manure and NPK fertilizer on PMK soil for the growth of oil palm seedlings at the main nursery stage. The study was conducted in Ngabang, West Kalimantan on January 17, 2022 to May 17, 2022. This study used a field experiment method with a completely randomized design (CRD) one factor, namely a combination of chicken manure and NPK fertilizer. The combinations in question are A= Chicken manure 0 % + 100 % NPK, B= Chicken manure 20 % + 80 % NPK, C= Chicken manure 40 % + 60 % NPK, D= Chicken manure 60 % + 40 % NPK, E= Chicken manure 80 % + 20 % NPK, F= Chicken manure 100 % + 0 % NPK. The variables observed in this study were plant dry weight (g), root volume (cm3), plant height (cm), stem diameter (cm), and number of leaves (strands). The growth response of oil palm seedlings in the main nursery on the 100 % NPK treatment was better than the 100 % chicken manure treatment on the variables of plant height, stem diameter and equally good on the variables of plant dry weight, root volume and number of leaves. Treatment of 100 % NPK resulted in the highest average plant dry weight, root volume, plant height, stem diameter and number of leaves compared to other treatments.